2015
DOI: 10.17116/repro2015214121-124
|View full text |Cite
|
Sign up to set email alerts
|

Сomparative evaluation of sperm DNA fragmentation and other sperm parameters

Abstract: Цель исследования-изучение корреляции между уровнем фрагментации ДНК сперматозоидов, интенсивностью акросомальной реакции и другими показателями фертильности эякулята. Материал и методы. Обследованы 56 мужчин, состоящих в бесплодном браке. Им был проведен комплексный анализ эякулята, включающий стандартное исследование с оценкой строгой морфологии по Крюгеру, а также определение индекса фрагментации спермальной ДНК (Halosperm), индуцируемости акросомальной реакции и концентрации позитивных по антиспермальным I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Giannoccaro et al noted a weak correlation between DNA fragmentation in stallion spermatozoa and their mobility and viability [15]. At the same time, other authors reported a negative effect of chromatin damage on the motility of human spermatozoa [16,17] and their fertilizing ability [1]. Our data support these observations, although the correlation between DNA fragmentation and either sperm motility or survival was more pronounced for thawed sperm than for the fresh one.…”
Section: Discussionsupporting
confidence: 84%
“…Giannoccaro et al noted a weak correlation between DNA fragmentation in stallion spermatozoa and their mobility and viability [15]. At the same time, other authors reported a negative effect of chromatin damage on the motility of human spermatozoa [16,17] and their fertilizing ability [1]. Our data support these observations, although the correlation between DNA fragmentation and either sperm motility or survival was more pronounced for thawed sperm than for the fresh one.…”
Section: Discussionsupporting
confidence: 84%
“…The structure of spermatozoa in the hybrids may be abnormal, as well: tail deformation (twisting or angular deformation) and a higher proportion of spermatozoa without a head. These changes can lead to the loss of the abilities to fertilize and to advance in the female genital tract [46].…”
Section: Discussionmentioning
confidence: 99%